A systematic review of the burden of pertussis in South Korea. Issue 6 (3rd June 2021) - Mungall, Bruce A.; Kim, Hyungwoo; Oh, Kyu-Bin
ABSTRACT: This review summarizes the published data on epidemiology and burden of pertussis in South Korea as these may be under-categorized. A systematic literature review of PubMed, SCOPUS, EMBASE and KMBASE was performed to identify published literature in South Korea since 2000. Pertussis detection rates among 19 eligible studies range from 0.7% to 100% across different age groups, detection methods and study settings. Highest rates are observed in infants, while adolescents and adults with pertussis infection may suffer from persistent coughing. Vaccination uptake of pertussis booster dose among adolescents and adults remains low while seropositivity (detection of anti-pertussis immunoglobulin G), is high among adults. This review reveals a high burden of vaccine-preventable pertussis in South Korea. Besides primary childhood vaccination, strategies like maternal immunization and decennial revaccination of adults should be considered. Active testing, reporting and better utilization of vaccine registries may provide insights for decision-makers nationwide. GA: